Pengaruh Covid-19 di Dunia Pendidikan - Nalla Afifah; Mita Nasywa Luthfiyyah; Sabila Safitri (Pusat Riset dan Inovasi Nasional, 2023)
At the beginning of 2020, a new type of virus (SARS-COV-2) was identified and the disease was called Corona Virus Disease 2019, which indicated that the first case came from Wuhan, China (Yuliana, 2020). By declaring the Covid-19 disease a global disaster, it can be said that the virus has had a negative impact on the world of education because learning is mostly held online because otherwise you will be infected with the Corona virus.